Changeability of the fully methylated status of the 15q11.2 region in induced pluripotent stem cells derived from a patient with Prader‐Willi syndrome. (22nd March 2017) - Okuno, Hironobu; Nakabayashi, Kazuhiko; Abe, Kousei; Ando, Takayuki; Sanosaka, Tsukasa; Kohyama, Jun; Akamatsu, Wado; Ohyama, Manabu; Takahashi, Takao; Kosaki, Kenjiro; Okano, Hideyuki
Abstract: Prader‐Will syndrome (PWS) is characterized by hyperphagia, growth hormone deficiency and central hypogonadism caused by the dysfunction of the hypothalamus. Patients with PWS present with methylation abnormalities of the PWS‐imprinting control region in chromosome 15q11.2, subject to parent‐of‐origin‐specific methylation and controlling the parent‐of‐origin‐specific expression of other paternally expressed genes flanking the region. In theory, the reversal of hypermethylation in the hypothalamic cells could be a promising strategy for the treatment of PWS patients, since cardinal symptoms of PWS patients are correlated with dysfunction of the hypothalamus. The genome‐wide methylation status dramatically changes during the reprograming of somatic cells into induced pluripotent stem cells (iPSCs) and during the in vitro culture of iPSCs. Here, we tested the methylation status of the chromosome 15q11.2 region in iPSCs from a PWS patient using pyrosequencing and a more detailed method of genome‐wide DNA methylation profiling to reveal whether iPSCs with a partially unmethylated status for the chromosome 15q11.2 region exhibit global methylation aberrations. As a result, we were able to show that a fully methylated status for chromosome 15q11.2 in a PWS patient could be reversed to a partially unmethylated status in at least some of the PWS‐iPSC lines. Genome‐wide DNA methylation profiling revealed that the partial unmethylation occurred at differentially methylated regions located in chromosome 15q11.2, but not at other differentially methylated regions associated with genome imprinting. The present data potentially opens a door to cell‐based therapy for PWS patients and, possibly, patients with other disorders associated with genomic imprinting.